As above, I do not know how to get the Laurent expansion of $\frac{e^{1/z^2}}{z-1}$ over 0. What I think I understand is splitting the denominator into $$ \frac{1}{z}\sum_0^\infty \frac{1}{z}^n + \frac{1}{z}\sum_0^\infty z^n $$

(I am not sure this is correct)

But then, what do I do about $e^{1/z^2}$? Clear steps and explanation would be very helpful!

  • 4
    $\begingroup$ The answer will depend on which annulus you are expanding over. $\endgroup$ – Lord Shark the Unknown May 17 at 1:53

By definition we have that $e^{1/z^2}=\sum_{k=0}^\infty\frac{z^{-2k}}{k!}$ for $z\neq 0$, and

$$\frac1{z-1}=-\sum_{k=0}^\infty z^k,\quad\text{ when } |z|<1\\ \frac1{z-1}=\frac1z\frac1{1-z^{-1}}=\frac1z\sum_{k=0}^\infty z^{-k}=\sum_{k=0}^\infty z^{-(k+1)},\quad\text{ when } |z|>1$$


$$\frac{e^{1/z^2}}{z-1}=\begin{cases}-\sum_{k=0}^\infty\sum_{j=0}^\infty \frac{z^{j-2k}}{k!}=\sum_{n\in\Bbb Z} c_n z^n,\quad 0<|z|<1\\ \sum_{k=0}^\infty\sum_{j=0}^\infty \frac{z^{-j-2k-1}}{k!}=\sum_{n\in\Bbb Z} b_n z^n,\quad |z|>1\end{cases}$$


$$c_n:=-\sum_{j,k\in\Bbb N:j-2k=n}\frac1{k!} \\b_n:=\sum_{j,k\in\Bbb N:-j-2k-1=n}\frac1{k!}$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.